THE IMPORTANCE OF DEVELOPING STUDENT YOUTH TRENDS THAT AFFECT MUSICAL PERCEPTION IN THE CONTEXT OF INNOVATIVE EDUCATION - A.Sultanov (American Journals Publishing, 2023)
This article examines the essence of the development of trends that affect the musical perception of student youth by improving the professional skills of future music teachers in the context of innovative education.
Keywords: Musical perception, tendency, transformation, musical creativity, Instrumental Performance, skill, innovative education, interactive, self-teaching, learning.